ISSUES OF INCREASING COGNITIVE ACTIVITY OF PRIMARY SCHOOL STUDENTS IN THE COURSE OF THE LESSON - Komolova, Shoxsanam (Educational Research in Universal Sciences, 2023)
This article covers the ways of improving the education and education of Primary School students of primary school teachers, issues of formation of cognitive activity of students, results of cognitive activity of students, methods of development of cognitive activity, various tasks of interactive didactic materials.